2022
DOI: 10.3390/buildings12060853
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Flood Intrusion Process under Malfunction of Flood Retaining Facilities in Complex Subway Stations

Abstract: In recent years, heavy rain and waterlogging accidents in subway stations have occurred many times around the world. With the comprehensive development trend of underground space, the accidents caused by flood flow intruding complex subway stations and other underground complexes in extreme precipitation disasters will be lead to more serious casualties and property damage. Therefore, it is necessary to conduct numerical simulation of flood intrusion process under malfunction of flood retaining facilities in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In physical modeling, researchers utilize hydrodynamic models to simulate flooding scenarios. For example, Edwar Forero-Ortiz [6] employed a 1D/2D hydrodynamic model, Zhiyu Lin [10] developed a 3D numerical simulation model based on the VOF (Volume of Fluid) model, Colombo [11] used a stochastic model that transformed a 3D numerical model, and Lyu [12] combined the stormwater management model SWMM (Storm Water Management Model) with the GIS (Geographic Information System) to simulate flood hazards in metro systems. On the other hand, statistical modeling approaches involve analyzing data and performing simulations based on statistical analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In physical modeling, researchers utilize hydrodynamic models to simulate flooding scenarios. For example, Edwar Forero-Ortiz [6] employed a 1D/2D hydrodynamic model, Zhiyu Lin [10] developed a 3D numerical simulation model based on the VOF (Volume of Fluid) model, Colombo [11] used a stochastic model that transformed a 3D numerical model, and Lyu [12] combined the stormwater management model SWMM (Storm Water Management Model) with the GIS (Geographic Information System) to simulate flood hazards in metro systems. On the other hand, statistical modeling approaches involve analyzing data and performing simulations based on statistical analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tang, Zhou [21] simulated the evacuation process of people after the subway station flooded, analyzed the influencing factors of safe escape, and obtained the critical escape water depth for people at the station. Lin, Hu [22] built a computational fluid dynamics model of a subway station, simulated the whole process of flood intrusion, and proposed the dangerous areas and evacuation routes under different water depths and invasion passages. Inoue, Toda [23] focused on the danger zone created at the staircase when the flood intrudes into the underground space and found that the flow rate and water depth of the flood on the staircase are closely related to the escape of people; they also proposed an escape judgment function, as follows:…”
Section: Introductionmentioning
confidence: 99%
“…In fact, epidemic prevention facilities are rarely mentioned in comprehensive disaster prevention and mitigation plans for cities around the world (20,21). Most of the studies about urban disaster facilities focus on assessing the ability of cities to cope with natural disasters from the perspectives of floods, fires, and earthquakes, combing with population data, urban infrastructure, social factors and so on (7,(22)(23)(24)(25). Existing studies indicate the characteristics and development trends of global urban disasters and major emergencies, comparing the advantages and disadvantages of urban disaster prevention facilities and conducting a macroscopic assessment of urban emergency measures to optimize the disaster prevention planning (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%